Multistep Fabrication of OECTs via Direct Ink Writing, With Performance Analysis Based on a Novel Measurement Protocol - Amir Mohammad Ghafari; Oskar Backman; Emil Rosqvist; Chunlin Xu; Luisa Torsi; Eleonora Macchia; Ronald Österbacka (Advanced Electronic Materials)
Abstract Organic electrochemical transistors (OECTs) have been proven beneficial for bioelectronic applications. However, the demand for reliable and fast fabrication methods has not yet been fully met. In this work, OECTs are fabricated using direct ink writing (DIW). This method is cleanroom‐free and can be done without using lithography techniques. These devices are characterized and benchmarked against devices fabricated using spin‐coating and drop‐casting deposition approaches. Response time as well as the product of carrier charge mobility and volumetric capacitance are found to be higher using the DIW fabrication approach compared to standard deposition techniques. In addition, a testing process is designed to systematically evaluate the operational degradation of the semiconductor channel. This test enables identical conditions for all tested devices while providing comparable output. Thicker channels show better stability, while thinner channels are proved to be better transistors. Finally, the degradation issues and instability of these devices are discussed.